Behavioral effects of academic pressure on the risk of adolescent idiopathic scoliosis: a case-control study - Qian Wang; Xinyun Li; Xinyao Liu; Nuo Chen; Ruoqi Dai; Hui Zhang; Yihui Du; Lilu Ding (Scientific Reports)
Abstract Adolescent idiopathic scoliosis (AIS) is a prevalent spinal deformity with significant health implications. While genetic and demographic factors are well-established, the influence of academic pressure and posture, especially in competitive educational environments, remains less understood. This case-control study analyzed data from a population-based AIS screening program, including 547 cases and 2735 matched controls. AIS cases were identified using the Adam’s forward-bending test and scoliometer measurements, with controls matched by age, sex, and school. Conditional logistic regression assessed the associations between academic pressure, sedentary behaviors, and AIS risk. Our study shows that early engagement in extracurricular activities before age five—common in competitive academic settings—raised the AIS risk with an OR of 2.18 (95% CI 1.03–4.61, P = 0.041). Students who spent time outdoors during school breaks had a 57% lower AIS risk (OR 0.43, 95% CI 0.20–0.92, P = 0.031) compared to those who stayed indoors, emphasizing the importance of physical activity during academic hours. Over two hours of daily outdoor physical activity reduced AIS risk by 48% (OR 0.52, 95% CI 0.28–0.97, P = 0.04), with a 65% reduction for more than three hours (OR 0.35, 95% CI 0.17–0.72, P = 0.005). Additionally, higher BMI was associated with an 8% lower AIS risk (OR 0.92, 95% CI 0.87–0.98, P = 0.006). Sedentary behaviors, such as watching television for over three hours daily, doubled AIS risk (OR 2.08, 95% CI 1.06–4.09, P = 0.033). These findings underscore the need for balanced educational policies that incorporate physical activity to reduce AIS risk among adolescents.